Analysis And the Factors That Influenced of Income in Beef Cattle Farm in Riung District of Ngada Regency Based on Dry Land - Kasimirus Barang; Obed Haba Nono; Arnoldus Keban (Buletin Ilmiah Impas, 2022)
A survey was carried out in Riung subdistrict Ngada District from 7 February 2018 until 30 May 2018 to analyse revenues and factors affecting cattle business in Riung District Ngada. Sampling is carried out gradually by determining the sample village in Purposif and continued with a randomized propotional determination. The number of respondents was 120 farmers. The accumulated Data is and subsequently carried out analysis of revenues and statistical analyses in the form of correlation and regression analyses. Revenue analysis results show that the average income of farmers in cattle livestock in Riung District Ngada Regency amounting to IDR. 4,609,650./year. Statistical analysis results showed that the cost factor of cage and equipment, labor and going have a real relationship with income and have a relationship pattern: Ŷ Y= 639,87 + 0,08x1 + 0,3x2 +5,56x3 + 11,01x4 and coefesien of determination (R²) = 0,672. But in partial test-T, it turns out that only X4 or health care costs that give a highly significantly (P < 0.01).